Maternal conceptions about remote learning for children with autism spectrum disorder during the pandemic - Olga Feitosa Braga Teixeira; Vera Lúcia Mendes de Paula Pessoa; Luciana Martins Quixadá; José Wagner Martins da Silva; Karla Corrêa Lima Miranda (Rev Rene, 2024)
Objective: to understand the challenges of remote learning for children with autism based on maternal perspectives. Methods: qualitative study conducted with 22 mothers from an association. Data collection involved participatory dynamics using the Comic Book Technique. French discourse analysis framework was used for material analysis. Results: the educational system's difficulty in addressing the uniqueness of children with autism had been an issue since their entry into school, and the pandemic exacerbated their exclusion. There was no adaptation to remote learning, and mothers chose to withdraw their children from school. The children's departure was ignored by teachers and school administration, and schools did not take responsibility for this population. Conclusion: the educational system was deemed inefficient in meeting the needs of these children during the pandemic. The lack of educational activities contributed to mental and emotional strain for the mother-child dyad and regression in the children’s skills and behaviors. Contributions to practice: maternal narratives should be considered and addressed by education professionals in the development of special education protocols, to guide and optimize educational practices in public health emergencies.